Why is group physical activity better? Empirical Evidence from Indonesian Islamic Primary Students - Nurkhozien, Mohammad; Rosidi, Sakban; Aswara, Agung Yuda; Sucipto, Adi (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2023)
This study aims to generate correlational-predictive knowledge for active participation in voluntary sports of Madrasah Ibtidaiyah (Islamic Primary School) students in Indonesia. This secondary study utilizes one of the newest collections of big data at the Center for Physical Literacy and Sports Education Studies, Postgraduate School of IKIP Budi Utomo. Of the 6,576 respondents to the sports culture survey for Indonesian students, 335 of them were Madrasah Ibtidaiyah students. From the proposed causal model, personal awareness, group norms, social support, and active participation in voluntary sports were selected for further analysis. The path analysis strategy found that the direct contribution of personal awareness to active sports participation was insignificant (0.020). The contribution of personal awareness indirectly, through social support (0.022), with a significant total effect (0.042). The findings of this study support the proposition about the importance of group norms and social support in improving voluntary sports for madrasah students.